Dynamic support evaluation to mitigate rock bursting in underground mines in central Peru - Sánchez Ormeño, Sergio (2024)
Accidents caused by rock bursting in underground excavations in the Peruvian mining sector pose a critical problem, leading to fatalities, machinery damage, and complete tunnel collapse. As mining activities reach greater depths, evaluating rock bursting becomes crucial. Various support systems have been employed to counteract these events, including dynamic bolts, dynamic mesh, and shotcrete on the slab. This research analyzes how these supports respond when rock mass releases accumulated energy under different conditions. Understanding their performance is vital for selecting appropriate reinforcement measures to enhance safety and mitigate the impact of rock bursts in underground mines.